Acute dissociative reaction to spontaneous delivery in a case of total denial of pregnancy: Diagnostic and forensic aspects. Issue 5 (20th October 2017) - Şar, Vedat; Aydın, Nazan; van der Hart, Onno; Steven Frankel, A.; Şar, Meriç; Omay, Oğuz
ABSTRACT: This article presents the history of a 21-year-old female college student with total denial of pregnancy who experienced an acute dissociative reaction during the spontaneous delivery at home without medical assistance where the newborn died immediately. Psychiatric examination, self-report questionnaires, legal documents, and witness reports have been reviewed in evaluation of the case. Evidence pointed to total denial of pregnancy, that is, until delivery. The diagnoses of an acute dissociative reaction to stress (remitted) and a subsequent PTSD were established in a follow-up examination conducted 7 months after the delivery. Notwithstanding the inherently dissociative nature of total denial of pregnancy, no other evidence has been found about pre-existing psychopathology. For causing the newborn's death, the patient faced charges for "aggravated murder, " which were later on reduced into "involuntary manslaughter." Given the physical incapacity to perform voluntary acts due to the loss of control over her actions during the delivery, and the presence of an acute dissociative reaction to unexpected delivery, the legal case represents an intricate overlap between "insanity" and "incapacitation" defenses. The rather broad severity spectrum of acute dissociative conditions requires evaluation of the limits and conditions of appropriate legal defenses by mental health experts and lawyers. Denial of pregnancy as a source of potential stress has attracted little interest in psychiatric literature although solid research exists which documented that it is not infrequent. Arguments are presented to introduce this condition as a diagnostic category of female reproductive psychiatry with a more neutral label: "unperceived pregnancy."